Kampung Pengawasan Partisipatif dan Road Map Indeks Kerawanan Pemilu di Kabupaten Indramayu - Dede Irawan (Jurnal Adhyasta Pemilu, 2022)
This study aims to determine the effectiveness of the participatory monitoring village program in preventing election violations. This research uses a qualitative method with a case study approach that analyzes the phenomenon of election supervision, election violations in the implementation of the 2019 Election and the 2020 Pilkada associated with the participatory monitoring village program which establishes the rambatan wetan village as a pilot project for the participatory monitoring center with the consideration that the wetan rambatan village is a zero village. offense and close to the city center. The results of the study show that the participatory monitoring village program does not consider data on election violations and the election vulnerability index in the 2020 elections so that its implementation is predicted to be less than optimal in preventing and suppressing election violations, the program should be mapped to villages with minimal knowledge, low participation and villages that have The potential for high vulnerability to violations is placed in several villages so that they can become a catalyst for Bawaslu in mapping and compiling an election vulnerability index in stages so that potential vulnerabilities can be prevented. The Participatory Monitoring Village Program should be optimized by paying attention to data on violations and vulnerabilities in order to prepare for the 2024 election design which is predicted to be very complex, because Election Oversight, potential violation vulnerabilities and the election vulnerability index are components that cannot be separated as an instrument of election supervision.